Equity in Science Education: A Comparative Analysis of Biology Laboratory Management in Urban and Rural Public Senior High Schools in Sumedang Regency - Yunita, Risma; Kurniatun, Taufani Chusnul; Prihatin , Eka (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Educational equity in biology education requires not only the formal availability of laboratories but also students’ access to functional equipment, safe practicum environments, institutional support, and opportunities to conduct inquiry-based activities. This exploratory comparative case study examined biology laboratory management in two A-accredited public senior high schools in Sumedang Regency, West Java: SMAN 1 Sumedang as an urban school and SMAN Rancakalong as a rural school. Data were collected from April to May 2026 through structured observation, semi-structured interviews, and document analysis. The interview component involved ten purposively selected participants consisting of two school administrators, two biology teachers who also served as laboratory managers, and six Grade XI students. The observation instrument included 48 indicators across 11 aspects of laboratory management. Data were analyzed thematically using Bafadal’s four management functions: planning, organizing, implementation, and supervision. The findings show that both schools experienced serious operational weaknesses despite their A accreditation status. Written laboratory schedules were absent, laboratory work programs were either unavailable or blank, no trained laboratory technician was assigned, only about six of 34 microscopes in the urban school and seven of 20 microscopes in the rural school were functional, laboratory documentation was outdated or unused, and occupational health and safety compliance reached only approximately 25%. The urban school had relatively better physical infrastructure, whereas the rural school experienced more severe limitations in students’ independent access to microscopes and authentic practicum activities. The study contributes case-based evidence that accreditation status may mask operational weaknesses in laboratory functionality and inequitable practicum access. Strengthening laboratory personnel, equipment maintenance, documentation, safety facilities, and accreditation indicators based on actual laboratory use is essential for improving equity in science education.